Analisis Konflik Ketenagakerjaan Terkait Hak Buruh dan Kewajiban Pada Kasus PT Alpen Food Industri - Desrina, Rania Adriane (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research investigates the implementation of labor law in Indonesia, with a focus on protecting labor rights and enforcing regulations in the relationship between employers and workers. PT Alpen Food Industry (AFI) was chosen as a case study. The research method used is qualitative, by analyzing in depth descriptive data such as company documents and interviews with related parties. The research results show that there are various violations of labor law by PT AFI, including wage cuts, the use of outsourced labor with wages below standard, and the denial of leave rights for pregnant female workers. Conflicts between companies and workers, especially through labor strikes, illustrate failures in law enforcement that result in injustice for workers. This study highlights the need for increased law enforcement, stricter work inspections, and better protection of workers' rights as steps to improve labor conditions in Indonesia. Key words: employment law, protection of workers' rights, enforcement of regulations, case studies, legal violations, law enforcement, work inspections, injustice, Indonesia.